2019
DOI: 10.1039/c8ta08391f
|View full text |Cite
|
Sign up to set email alerts
|

Fluorinated polysulfonamide based single ion conducting room temperature applicable gel-type polymer electrolytes for lithium ion batteries

Abstract: Single ion conducting polymer electrolytes (SIPEs) comprised of homopolymers containing a polysulfonylamide segment in the polymer backbone are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
84
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(96 citation statements)
references
References 81 publications
(158 reference statements)
7
84
1
Order By: Relevance
“…During charging, lithium ions convey a current from the positive to negative electrode through the electrolyte, which is reversed during discharging. LIBs have already become well‐liked rechargeable batteries as a predominant power source for portable electronics because of their comparatively higher energy density, good cycle life, and power performance . Meanwhile, at present, the available lithium resources in the earth's crust are limited, and the estimated lithium mean mass fraction is only 20 ppm.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During charging, lithium ions convey a current from the positive to negative electrode through the electrolyte, which is reversed during discharging. LIBs have already become well‐liked rechargeable batteries as a predominant power source for portable electronics because of their comparatively higher energy density, good cycle life, and power performance . Meanwhile, at present, the available lithium resources in the earth's crust are limited, and the estimated lithium mean mass fraction is only 20 ppm.…”
Section: Introductionmentioning
confidence: 99%
“…LIBs have already become well-liked rechargeable batteries as ap redominant power source for portable electronics because of their comparatively higher energy density,g ood cycle life, and power per-formance. [20][21][22] Meanwhile, at present, the available lithium resources in the earth's crust are limited, and the estimated lithium mean mass fraction is only 20 ppm. The cost of lithium resources is rapidlyi ncreasing because of their tremendousu se in industrial areas.…”
Section: Introductionmentioning
confidence: 99%
“…All considered PVdF-HFP blended SIPE membranes exhibit different polymer architectures, solvent solutions, and membrane compositions (other major characteristics of the polymer blends are collected in Table S1 , see Supplemental Information ) ( Zhang et al., 2014a ; Sun et al., 2014 ; Zhang et al., 2014b ; Qin et al., 2015 ; Rohan et al., 2015 ; Liu et al., 2016 ; Pan et al., 2016 ; Zhang et al., 2017a , 2017b ; Dong et al., 2018 ; Li et al., 2018 ; Chen et al., 2018 ; Li et al., 2019 ). The obtained morphologies of polymer electrolyte membranes similarly prepared from solution casting varied from highly porous (micrometer-sized pores) ( Sun et al., 2014 ; Zhang et al., 2014a , 2014b ; Pan et al., 2015 , 2016 ; Rohan et al., 2015 ; Zhang et al., 2017a , 2017b , 2018 ; Dong et al., 2018 ; Chen et al., 2018 ; Li et al., 2019 ) to rather dense structures (nanometer-sized pores), ( Zhang et al., 2014a , 2014b ; Qin et al., 2015 ; Liu et al., 2016 ; Pan et al., 2016 ; Li et al., 2018 ; Borzutzki et al., 2019 ), with no clear trend for different SIPE structures. Note, though, that a homogeneous membrane morphology is considered beneficial to prevent the formation of inhomogeneous high-surface-area (“needle-like” or “dendritic”) lithium (HSAL [ Winter et al., 2018 ]) deposits that otherwise could grow throughout the pore structures, eventually yielding short circuits within the cells ( Zhang, 2018 ; Lagadec et al., 2019 ).…”
Section: Resultsmentioning
confidence: 97%
“…Subsequent studies were further focused on charge delocalization by bonding of electron‐withdrawing groups to sulfonate fragment (Scheme , 4 , 5 , 6 ). Afterwards came the era of SICs incorporating anions structurally similar to the well‐known bis(trifluoromethylsulfonyl)imide (TFSI) ion (Scheme , 7 , 8 , 9 , 10 , 12 ). This was later extended by the development of PILs bearing the so‐called ‘super‐TFSI’ anion (Scheme , 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it was revealed that to increase the ion conductivity it is preferable to place the anion in the side chain rather than in polymer backbone (Scheme , 7 , 9 , 11 , 12 ). The longer the spacer between the attached anion and main polymer chain the higher is the conductivity (Scheme , 7 , 8 ).…”
Section: Introductionmentioning
confidence: 99%